The Disturbed Outer Milky Way Disc for Stars With Measured Line-Of-Sight Velocity - Mwaniki, Patrick Njoroge; Wamalwa, Dismas Simiyu (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The Milky Way’s disc has been disturbed in the outer parts affecting the movements of stars. Using the position and proper motion measurements for 33 million stars in line-of-sight from Gaia DR3 we estimated a relationship between their vertical velocity and angular momentum around the galactic center. From the density distribution, the vertical velocity for stars in the disc at a galactic radius between 10 to 14 kpc is strongly dependent on the angular momentum. However, a break or bimodality is visible in the vertical velocity distribution, particularly around 11.5 kpc ( 2700 kpc km/s). This bimodality has a downturn in vertical velocity at 10 kpc ( 2400 kpc km/s) to a minima at 11.5 kpc ( 2700 kpc km/s) followed by an abrupt break rising to a positive value. Main sequence stars are strongly affected by the disturbances in their vertical velocities. N-body simulations simulated that the passage of a Sagittarius-like dwarf galaxy can generate similar disturbances in the Galactic disc.